If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -8 = 7 + -12x + 9 Reorder the terms: -8 + 12x = 7 + -12x + 9 Reorder the terms: -8 + 12x = 7 + 9 + -12x Combine like terms: 7 + 9 = 16 -8 + 12x = 16 + -12x Solving -8 + 12x = 16 + -12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12x' to each side of the equation. -8 + 12x + 12x = 16 + -12x + 12x Combine like terms: 12x + 12x = 24x -8 + 24x = 16 + -12x + 12x Combine like terms: -12x + 12x = 0 -8 + 24x = 16 + 0 -8 + 24x = 16 Add '8' to each side of the equation. -8 + 8 + 24x = 16 + 8 Combine like terms: -8 + 8 = 0 0 + 24x = 16 + 8 24x = 16 + 8 Combine like terms: 16 + 8 = 24 24x = 24 Divide each side by '24'. x = 1 Simplifying x = 1
| a^8b-a^4b^3+a^3b^6-a^3b^3=0 | | (2x+24)(x-6)= | | 12x^3+47x^2+11x= | | 3p+5=8 | | 2v^2+36=17v | | 3b^2-8b-16= | | X+2x+x-x=1x+7-2x+3x | | 7(15)-4=5(15) | | 5(3+y)=5(y+3) | | (5x+10)=3 | | (x^2+3)(x^2-3)= | | Abd=adb | | 5(3x+7)=15-10(2-x) | | h=-16t^2+48t+8 | | N+5=19 | | 5x+(-5x)=0 | | H(t)=-5t^2+45t | | 8x^3+2xy+9-5x^3+xy-1= | | 10=x(2) | | 0=x^2+11x+35 | | 2cos^2x=13sinx-5 | | 2x+2.4=8.2 | | 2(2u+6)-u= | | 133+8m=245 | | -4(r-4)=-48 | | 1/6(x-4)=1/3(2x+4) | | 22n-133=285 | | y=(100)(1/100) | | 4x+81=180 | | 2(b-6)=-60 | | 7(-x-3)-(x-5)=31 | | 3x^2+8x=5-6x |